Selective detection of chemical warfare agents VX and Sarin by the short wavelength inner filter technique (SWIFT). Issue 95 (16th November 2020) - Redy Keisar, Orit; Pevzner, Alexander; Baheti, Abhishek; Vigalok, Arkadi; Ashkenazi, Nissan
Abstract : A novel SWIFT-based strategy for selective fluorimetric detection of practical amounts of V and G chemical warfare agents is reported. Abstract : A novel SWIFT-based strategy for fluorimetric detection of practical amounts (minimal effective dose or lower) of chemical warfare agents is reported. This strategy employs readily available reagents and allows distinguishing between the V and G agents, as well as their discrimination from potential interferents.